2021
DOI: 10.3390/ijms222111692
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of TaGS3 Differentially Regulates Grain Weight and Size in Bread Wheat

Abstract: The heterotrimeric G-protein mediates growth and development by perceiving and transmitting signals in multiple organisms. Alternative splicing (AS), a vital process for regulating gene expression at the post-transcriptional level, plays a significant role in plant adaptation and evolution. Here, we identified five splicing variants of Gγ subunit gene TaGS3 (TaGS3.1 to TaGS3.5), which showed expression divergence during wheat polyploidization, and differential function in grain weight and size determination. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…AS is involved in most of the plant processes, including plant growth, development, and responses to external cues [ 47 ]. The function of AS on grain filling and yield has been a research hotspot for many years [ 26 , 27 , 48 , 49 , 50 , 51 , 52 ]. A single mutation at the 5′splice site of Waxy affects the alternative splicing of its pre-mRNA, resulting in the reduced levels of amylose [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS is involved in most of the plant processes, including plant growth, development, and responses to external cues [ 47 ]. The function of AS on grain filling and yield has been a research hotspot for many years [ 26 , 27 , 48 , 49 , 50 , 51 , 52 ]. A single mutation at the 5′splice site of Waxy affects the alternative splicing of its pre-mRNA, resulting in the reduced levels of amylose [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing of OsLG3b has also been reported to control grain length and yield in rice [ 50 ]. When TaGS3 undergoes AS, it produces five splicing variants, resulting in opposite effects on grain weight and grain size [ 51 ]. Recently, a study also demonstrated that the AS of GS1;1 affects grain amylose content and sugar metabolism in rice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…AS can generate truncated proteins, disrupting main domains to form non-functional proteins ( Kalyna et al., 2012 ) or annulling interaction with other proteins and thereby impeding the formation of functional protein complexes ( Qin et al., 2017 ). Moreover, some splicing variants can antagonistically compete with other variant and interfere with its function in a negative manner ( Posé et al., 2013 ; Ren et al., 2021 ). Increasing evidences have demonstrated that AS participates in the regulation of plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…The genome-wide AS profiling uncovered a very complex AS landscape in wheat, exhibiting that almost 22% of genes occur AS ( Yu et al., 2020 ). Increasing evidences have uncovered that AS events in wheat are enormously related to grain-related traits such as polyphenol oxidase activity ( Sun et al., 2010 ), starch synthase activity ( Zhou et al., 2018 ), and grain weight and size ( Ren et al., 2021 ). AS is also related to abiotic stresses tolerance ( Egawa et al., 2006 ; Liu et al., 2018 ) and disease resistance ( Wang et al., 2020 ; Sánchez-Martín et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the same topic, Ren et al [6] studied a candidate gene for the yield component of grain weight and size in bread wheat. The authors identified five splicing variants of the Gγ subunit gene TaGS3 (TaGS3.1 to TaGS3.5), which showed expression divergence during wheat polyploidization and a differential function in grain weight and size determination.…”
mentioning
confidence: 99%